2019
DOI: 10.5014/ajot.2019.030130
|View full text |Cite
|
Sign up to set email alerts
|

Combining Virtual Reality Motor Rehabilitation With Cognitive Strategy Use in Chronic Stroke

Abstract: Importance: Rehabilitation interventions for chronic stroke are largely impairment based, with results confined to the level of impairment instead of function. In contrast, cognitive strategy training interventions have demonstrated clinically meaningful improvements in functional outcomes. Integration of these approaches has yet to be explored. Objective: To evaluate acceptability, recruitment, and retention rate and determine which outcome measures best capture the effect of the intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Also, the lack of real-time data about the patient performance and improvements contribute to the non-optimal therapy development [43,44]. Previous works have shown evidence of the VR technologies efficacy in rehabilitation [45][46][47][48], enhancing therapies with diverse immersive technologies that allow the users to hear, see, perceive haptic feedback, and navigate in interactive environments. VR and exoskeletal systems have been used together to enhance functional exercising [49][50][51], however, these technologies have been scarcely studied in immersive environments.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the lack of real-time data about the patient performance and improvements contribute to the non-optimal therapy development [43,44]. Previous works have shown evidence of the VR technologies efficacy in rehabilitation [45][46][47][48], enhancing therapies with diverse immersive technologies that allow the users to hear, see, perceive haptic feedback, and navigate in interactive environments. VR and exoskeletal systems have been used together to enhance functional exercising [49][50][51], however, these technologies have been scarcely studied in immersive environments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies had developed games customized to the abilities of stroke patients and reported positive effects on their motor recovery [ 42 , 50 , 53 , 56 , 61 , 62 ]. These results are in line with the findings of other researches [ 25 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, the study size is limited to 10 patients. However, recent related studies of patients with chronic stroke with 10 participants have yielded clinically valuable results and contributions [21,22].…”
Section: Discussionmentioning
confidence: 99%